Library work for children and young adults in the developing countries : proceedings of the IFLA/UNESCO pre-session seminar in Leipzig, GDR, 10-15 August, 1981 - Patte, Geneviève.; Sigrún Klara Hannesdóttir. (München ; New York : K.G. Saur, 1984)
The International Federation of Library Associations and Institutions (IFLA) is the leading international body representing the interests of library and information services and their users. It is the global voice of the information profession. The series IFLA Publications deals with many of the means through which libraries, information centres, and information professionals worldwide can formulate their goals, exert their influence as a group, protect their interests, and find solutions to global problems.
Frontmatter -- CONTENTS -- PREFACE -- INTRODUCTION -- ROLE AND FUNCTIONS OF LIBRARY SERVICES FOR CHILDREN IN THE DEVELOPMENT OF RURAL AND URBAN COMMUNITIES / ROLE DE LA BIBLIOTHEQUE POUR ENFANTS DANS LE DEVELOPPEMENT DES COMMUNAUTES RURALES ET URBAINES -- PLACE OF CHILDREN'S SERVICES IN NATIONAL NETWORKS / PLACE DES SERVICES POUR ENFANTS A L'INTERIEUR DES RESEAUX NATIONAUX -- CHILDREN'S LIBRARIES AND PROMOTION OF LOCAL LITERATURE AND PUBLISHING / LES BIBLIOTHEQUES POOR ENFANTS ET LA PROMOTION D'UNE LITTERATURE ET D'UNE EDITION LOCALE -- EDUCATION AND TRAINING OF CHILDREN'S LIBRARIANS: A ROUND TABLE DISCUSSION / TABLE RONDE SUR LA FORMATION PROFESSIONNELLE DES BIBLIOTHECAIRES POUR ENFANTS -- Recommendations / Recommandations -- List of other papers / Liste des autres communications -- List of participants / Liste des participants -- Backmatter.
English and French.
Includes bibliographical references.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Children's libraries -- Developing countries -- Congresses; Young adults' libraries -- Developing countries -- Congresses; Children -- Books and reading -- Developing countries -- Congresses; Young adults -- Books and reading -- Developing countries -- Congresses; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- Archives & Special Libraries; Children -- Books and reading; Children's libraries; Young adults -- Books and reading; Young adults' libraries; Developing countries; Bibliotheken; Jeugd; Conference papers and proceedings